Cutting‐edge advancements of nanomaterials for medi‐translatable noninvasive theranostic modalities. Issue 3 (28th January 2021) - Zhang, Chen; He, Weixin; Liu, Chenxi; Jiao, Dian; Liu, Zhe
Abstract: Disease‐oriented theranostic modalities have witnessed rapid developments in the past decade, and some of them are on the road of medi‐translation for successful clinical utilities. Thanks to their unprecedented convenience, minimized side‐effect, satisfactory prognosis, and good controllability by external sources such as light, sound, electricity, heat and magnetism, recent advancements on noninvasive theranostic modalities have opened up a new window for the dawn and light‐shedding of cutting‐edge functional nanomaterials in association with current commercialized clinical devices to serve precision and visualized medicine for new‐generation disease‐oriented healthcare resolutions. This review summarizes the latest progresses on the advanced nanomaterial developments as well as their emerging applications to image‐based diagnosis and noninvasive treatments by external stimuli sources. Furthermore, their state‐of‐the‐art biomedical translations have been highlighted to outlook the prevailing trends for clinical uses, and current challenges are discussed for sake of comprehensive safety issues before to humans. Abstract : Advanced noninvasive theranostic modalities have found emerging applications in association with functional nanomaterials and visualized strategies to discriminate diseased tissues and lesion margins for precision medicine